Five new species of the genus Tripylella (Nematoda: Enoplida: Tripylidae) - Prado-Vera, I. C. D.; Ferris, H.; Nadler, S. A. (Zootaxa, 2016)
Five new species of the genus Tripylella are described, two from México, one from Fátima, Portugal, one from Quito,Ecuador, and one from California, USA. Tripylella mexicana sp. n. is characterized by its short body (average 0.74 mm), short pharynx (average 161 µm), short tail (average 117 µm), presence of an excretory pore and small setae distributed sparsely along the body, the presence of body pores, the posterior position of the subventral teeth in relation to the small dorsal tooth with all teeth in contiguous stomal chambers, the finely-striated cuticle with many anastomoses, the non-protruding vulval lips, and the presence of sclerotized pieces in the vulval region. Tripylella muscusi sp. n. is characterized by its body length (average 0.94 mm), pharynx length (average 201 µm), tail length (average 140 µm), the anterior position of the subventral teeth in relation to the small dorsal tooth in a single stomal chamber, the presence of an excretory pore, the presence of body pores and sparse somatic setae, the finely-striated cuticle with sparse anastomoses, protruding vulval lips and sclerotized oval-shaped pieces present in the vulval region. Tripylella quitoensis sp. n. is characterized by the short body length (average 0.72 mm), the short outer labial setae, the short pharynx (average 175 µm), the location of the anterior subventral teeth and posterior dorsal tooth in the same stomal chamber, the short tail (average 98 µm), the apparent absence of an excretory pore, presence of body pores, presence of somatic setae, a finely-striated cuticle, non-protruding vulval lips, and very small oval sclerotized pieces in the vulva. Tripylella fatimaensis sp. n. is characterized by the short body, (average 0.74 mm) long, by the length of the pharynx (average 180 µm), the length of the tail (average 110 µm) and in the length of its reduced diameter portion, 45–58 µm, the presence of an excretory pore, body pores and three pairs of caudal setae (one pair each latero-ventral, latero-dorsal and ventral). Tripylella dentata sp. n. is characterized, and differs from all the species of the genus, by the presence of two adjacent stomal chambers, with two large teeth, one dorsal and one ventral, in the posterior stomal chamber and two subventral teeth in the anterior smaller chamber, short body (average 0.85 mm), pharynx length (average 209 µm), tail length (average 115 µm), the apparent absence of an excretory pore, the presence of two cervical setae in a lateral position, and by the presence of conspicuous pores along the body.